SOSKOPOP Haloze: a decision support system for potential claimants of grassland-targeted agri-environment measures - Ivajnšič, Danijel; Pintarič, David; Škornik, Sonja; Kaligarič, Mitja; Pipenbaher, Nataša (Journal for Geography, 2019)
The agri-environment measures (KOPOP) are intended to preserve and promote special agricultural practices that contribute to preserving biodiversity and landscape, protect water resources, and contribute to mitigation and adaptation to climate change through adaptation of farming. Current studies show that the integration of agricultural holdings in the KOPOP measures is negligible, especially at the level of high nature value grasslands, despite the great potential, at the national level. For this reason, we developed a web and mobile application that would primarily inform owners whose grassland areas can be included in a KOPOP sub-measure and how much monetary compensation can they receive if they choose to join. The response of the first users was very positive, but of course, the involvement of agricultural holdings in the KOPOP measures is highly correlated with the monetary compensation, which is significantly undermined in the current program 2014-2020. Nevertheless, such information systems could contribute to a better implementation of the KOPOP measures in the forthcoming scheme of the European Agricultural Fund for Rural Development 2021-2026, not only in the field of grassland, but also in other nature conservation-relevant habitats.